Sinterização de finos de resíduos de construção civil: uma contribuição para o desenvolvimento sustentável - Paula Gisele Lamezon de Padua (2008)
The sintering of ore is a metallurgic process, in which iron ore fine, non-iron ore and fusiagent are agglomerates by partial fusion. The product of this process is a porous material that can be used in blast furnace. In this paper, it is assessed the possibility to use the same process to agglomerate demolition and construction waste fine. Samples of fine of mortar or fine demolition and construction waste, coke, blast furnace granulated slag, limestone and water were mixed, pelletized and sintered in appropriated equipments. The dates obtained show not is possible to sinter fine of mortars. Therefore, concerning, the compressive strength, module of elasticity and water absorption, is possible to substitute in the made mortar to concrete the nature sand to sinter made of fine demolition waste, blast furnace slag, coke, limestone and water, in the proportions of 45,5%, 22,75%, 9%, 22,75% e 2 l. These results propose in the situations of necessary to expend of fines demolition and construction waste be priority the sintering can be a solution to be analyzed, in the society visa the sustainable development yet is technically viable.